A new endemic cave dwelling species of Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) in Kien Giang Biosphere Reserve, Southwestern Vietnam - Tri, Ngo Van; Grismer, L. Lee; Grismer, Jesse L. (Zootaxa, 2008)
A new endemic cave-dwelling species of gekkonid lizard, Cyrtodactylus hontreensis sp. nov., is described from Hon Tre Island in Kien Giang Biosphere Reserve in southwestern Vietnam and differentiated from all other species by a unique suite of the following characters: SVL of 79.7 ± 4.9 mm, three broad transverse dorsal body bands edged in white between limb insertions, very low smooth dorsal body tubercles, the absence of a precloacal groove, 7–8 precloacal pores arranged in a chevron in males, a shallow dorsal groove on the tail, absence of caudal tubercles, and various aspects of color pattern.